2017
DOI: 10.1186/s12881-017-0427-2
|View full text |Cite
|
Sign up to set email alerts
|

Novel APC gene mutations associated with protein alteration in diffuse type gastric cancer

Abstract: BackgroundThe role of adenomatous polyposis coli (APC) gene in mitosis might be critical for regulation of genomic stability and chromosome segregation. APC gene mutations have been associated to have a role in colon cancer and since gastric and colon tumors share some common genetic lesions, it is relevant to investigate the role of APC tumor suppressor gene in gastric cancer.MethodsWe investigated for somatic mutations in the Exons 14 and 15 of APC gene from 40 diffuse type gastric cancersamples. Rabbit poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…CRC and GC share the same spectrum of the APC gene mutation, exons 14 and 15 are the most frequently mutated region for both cancers (Smith et al, 2002;Fornasarig et al, 2018). Ghatak et al, (2017) have demonstrated novel APC gene changes in diffuse type of GC related to cell cycle abnormalities and expression of APC protein. Tunisian patients with GC had positive APC expression in 68.7%, β-catenin in 77.5% (Ayed-Guerfali et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…CRC and GC share the same spectrum of the APC gene mutation, exons 14 and 15 are the most frequently mutated region for both cancers (Smith et al, 2002;Fornasarig et al, 2018). Ghatak et al, (2017) have demonstrated novel APC gene changes in diffuse type of GC related to cell cycle abnormalities and expression of APC protein. Tunisian patients with GC had positive APC expression in 68.7%, β-catenin in 77.5% (Ayed-Guerfali et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…APC is a tumor suppressor gene that has a key role in several molecular processes, such as suppression of canonical Wnt signaling[ 25 ], and the presence of APC mutations have been demonstrated in gastric adenocarcinoma samples[ 26 , 27 ]. APC gene mutations have been reported in both intestinal and diffuse types of gastric carcinoma with a higher frequency in the intestinal subtype of the disease[ 28 , 29 ]. The adenoma to carcinoma transition pathway has a 20% APC mutation in the intestinal type of gastric carcinoma[ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The human adenomatous polyposis coli ( APC ) gene is located on the long (q) arm of chromosome 5, encoding a 312 kDa protein with 2,843 amino acids (Ghatak et al, 2017). APC protein is well conserved between mammals and fruit flies and well‐known as a tumor suppressor.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that most cases of colorectal cancer (CRC) are initiated by inactivation mutations in the APC gene (Tanaka et al, 2017; Yedid et al, 2016; L. Zhang & Shay, 2017). Meanwhile, gastric and colon tumors have some common genetic lesions (Ghatak et al, 2017), so it is valuable to investigate the role of the APC tumor suppressor gene in GC. Furthermore, via miRNA microarrays, we found that APC is a predictive target gene of miRNA‐192 and ‐215.…”
Section: Introductionmentioning
confidence: 99%